COVID‐19 and paediatric health services: A survey of paediatric physicians in Australia and New Zealand. (4th May 2020) - Foley, David A; Kirk, Michael; Jepp, Catherine; Brophy‐Williams, Sam; Tong, Steven Y C; Davis, Joshua S; Blyth, Christopher C; O'Brien, Matthew P; Bowen, Asha C; Yeoh, Daniel K; ,
Abstract : Aims: COVID‐19 is now a global pandemic. At the time of survey, fewer than 150 children in Australia and New Zealand had documented infection. The aim of this study was to assess attitudes, readiness and confidence in the early stages of the COVID‐19 pandemic through an online survey of paediatric physicians and sub‐specialists across Australia and New Zealand. Methods: Multiple email list groups were used to contact paediatric physicians to undertake an online Likert scale survey between 17 and 24 March. Respondents' specialty, experience and work setting were recorded. Ordinal logistic regression was used to determine respondent factors. Results: There were 542 respondents from across Australia and New Zealand: an estimated 11% of the paediatric physician workforce. A minority (36.6%) agreed that their national response had been well coordinated; the majority (92.7%) agreed that senior‐level hospital administrators were taking the situation seriously. Most reported a good understanding of the natural history of COVID‐19 in children, and knowledge of where to find local information. A large proportion of physicians (86.1%) were worried about becoming infected through their work; few (5.8%) reported that they would not come to work to avoid infection. Closure of school and childcares would reduce the ability to continue work at current capacity for 23.6% of respondents. Conclusion: Despite limited experience in pandemics, most paediatric physicians felt informed. Concern about exposure at work is common; most were willing to work regardless. The closure of schools and daycares may have an impact on staffing. Coordination and leadership will be critical.